Psychosocial Health of the Badjao People During COVID-19 in Jolo, Philippines: An Exploratory Study - Zhendra T. Masong; Hamdoni K. Pangandaman (Nurse Media: Journal of Nursing)
Background: The Badjao, a nomadic maritime group in Southeast Asia, faces heightened vulnerability during public health crises due to their reliance on maritime livelihoods, limited healthcare access, and historical marginalization – challenges exacerbated by the COVID-19 pandemic. However, there is a significant research gap in understanding their unique needs and vulnerabilities, especially its specific impacts on their health and well-being due to the pandemic.